Design of a flexible digital baseband signal processing algorithm - Mohamad, Rosalina; Harun, Harlisya; Nuzli, Mohamad Anas; Dimyati, Kaharudin (Federation of Engineering Institutions of Islamic Countries, 2006)
The work presented in this paper is aimed at designing a flexible digital baseband signal processing algorithm (DBSP) for satellite applications. In non-real-time application, there have been many examples or simulations of DBSP, written in C language but the problem is, most of them requires many loops to execute and hence, cause timing problem. Thus, this is not suitable for real-time application. In this paper, we show how we solved the problem by satisfying several requirements simultaneously: 1) removing loop or complicated algorithm in DBSP functions with flexible DBSP algorithm 2) using DSP-BIOS Scheduling module to increase performance and make sure our sample data are in packed. We also implement this algorithm on DSP TMS320C6711 from Texas Instruments and the result shown in this paper is based on CPU (Central Processing Unit) performance of DBSP functions that can be calculated using DSP-BIOS Instrumentation Module. Performance comparisons between the existing algorithm and the proposed algorithm are proven in terms of cycle count and real-time capability.